1994
DOI: 10.1002/cne.903450410
|View full text |Cite
|
Sign up to set email alerts
|

Expression of GAT‐1, a high‐affinity gamma‐aminobutyric acid plasma membrane transporter in the rat retina

Abstract: Gamma-aminobutyric acid (GABA) plasma membrane transporters influence synaptic transmission by high-affinity, Na(+)-dependent transport processes. The cDNA clone, GAT-1, encodes a high-affinity Na(+)- and Cl(-)-dependent GABA plasma membrane transporter, which has kinetic and pharmacological properties similar to those of high-affinity GABA uptake systems associated with neurons. The present study evaluates the distribution and cellular localization of this putative neuronal GABA transporter by RNA blot hybrid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
58
1

Year Published

1996
1996
2005
2005

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 80 publications
(72 citation statements)
references
References 65 publications
13
58
1
Order By: Relevance
“…GAT3 immunoreactivity was primarily seen in Mü ller cells but also in the somata and processes of amacrine cells. Our observations in rabbit retina are in accordence with results obtained in rat and mouse (Brecha & Weigmann 1994;Ruiz et al 1994;Honda et al 1995;Johnson et al 1996). Double labeling showed that GAT3 immunoreactivity was present in pillarlike cells, which were also labelled with the vimentin antibody, which is a well accepted marker for Mü ller cells.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…GAT3 immunoreactivity was primarily seen in Mü ller cells but also in the somata and processes of amacrine cells. Our observations in rabbit retina are in accordence with results obtained in rat and mouse (Brecha & Weigmann 1994;Ruiz et al 1994;Honda et al 1995;Johnson et al 1996). Double labeling showed that GAT3 immunoreactivity was present in pillarlike cells, which were also labelled with the vimentin antibody, which is a well accepted marker for Mü ller cells.…”
Section: Discussionsupporting
confidence: 92%
“…In adult rat and mouse retina, GAT1 and GAT3 immunoreactivity is present in amacrine cells, in displaced amacrine cells and in processes in the inner plexiform layer (Brecha & Weigmann 1994;Ruiz et al 1994;Honda et al 1995;Johnson et al 1996). GAT3 is also present in Mü ller cells.…”
Section: Discussionmentioning
confidence: 99%
“…The immunoreactivity of GAT3 is strong in Mü ller cells, whereas GAT1 immunoreactivity is only weak in them. This result has been confirmed by in situ hybridisation, which demonstrated that the GAT1 mRNA content was lower in Mü ller cells than in neurons (Brecha & Weigmann, 1994).…”
supporting
confidence: 56%
“…GAT1 and GAT3 immunoreactivities are present mainly in amacrine cells, displaced amacrine cells and in the inner plexiform layer (IPL) (Brecha & Weigmann, 1994;Ruiz et al 1994;Honda et al 1995;Johnson et al 1996). GAT2 labeling is present in the optic nerve and the retinal pigment epithelium cells.…”
mentioning
confidence: 99%
“…To date, there is no support for a transporter-mediated mechanism in mammalian horizontal cells. For example, GATs have not been localized to rodent and rabbit horizontal cells (Brecha and Weigmann, 1994;Johnson et al, 1996;Hu et al, 1999), and patchclamp recordings of isolated mammalian (rabbit and mouse) horizontal cells have not revealed the presence of GABA-dependent transporter currents (Blanco et al, 1996;Feigenspan and Weiler, 2004). Finally, no highaffinity transport of [ 3 H] GABA or GABA analogs by horizontal cells has been reported for any adult mammalian retina (Ehinger, 1977;Blanks & Roffler-Tarlov, 1982;Mosinger and Yazulla, 1985;Wä ssle & Chun, 1988Löhrke et al, 1994).…”
Section: Transmitter Release From Horizontal Cellsmentioning
confidence: 99%